Natural polyphenol mangiferin delays neuronal cell senescence by inhibiting neuroinflammation mediated by microglial activation - Wei Nong; Xiaoli Chen; Yixin Chen; Xueping Feng; Wen Kong; Rui Chi; Li Yan; Zhiquan Wei (IBRO Neuroscience Reports)
Extracellular β-amyloid protein (Aβ) plaques are prominent pathological feature of Alzheimer's disease (AD). Aβ oligomers and plaques induce sustained microglial activation via the adenosine monophosphate-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR)/interferon regulatory factor 5 (IRF5) signaling pathway. This microglial activation-mediated neuroinflammation can accelerate neuronal cell senescence. Consequently, the regulation of the AMPK/mTOR/IRF5 pathway presents a potential therapeutic target for AD, as it may inhibit neuroinflammation and delay neuronal cell senescence. Mangiferin, a bioactive natural polyphenol extracted from the leaves of Mangifera indica Linn., has garnered significant attention for its anti-inflammatory properties. However, it remains unclear whether mangiferin can modulate the AMPK/mTOR/IRF5 pathway to inhibit microglial activation-mediated neuroinflammation and delay neuronal cell senescence. This study employed both cellular and animal models of neuronal cell senescence to explore the effects of mangiferin on the regulation of the AMPK/mTOR/IRF5 pathway, aiming to inhibit neuroinflammation and delay neuronal cell senescence in vitro and in vivo. Specifically, SH-SY5Y neuroblastoma cells were subjected to a neuroinflammatory microenvironment induced by Aβ1–42-mediated HMC3 microglial activation to induce neuronal cell senescence in vitro. Additionally, SAMP8 accelerated aging mice were utilized as an aging animal model. The results indicate that mangiferin significantly enhances AMPK phosphorylation in microglial cells, inhibits mTOR activation, and downregulates IRF5 expression. These effects collectively suppress microglial activation and markedly reduce the production of pro-inflammatory cytokines by activated microglia. Consequently, there is a decrease in the proportion of neurons arrested in the G0/G1 phase and a reduction in the number of senescence-associated β-galactosidase (SA-β-gal) positive neurons. Furthermore, mangiferin significantly decreases the expression of neuronal cell senescence markers P16Ink4a and P21Cip1. Collectively, these findings suggest that mangiferin effectively regulates the AMPK/mTOR/IRF5 pathway, inhibits neuroinflammation mediated by microglial activation, and delays neuronal cell senescence. This study underscores the potential of mangiferin for the treatment of neuroinflammation and neurodegenerative diseases.